1984
DOI: 10.1159/000233527
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Mixed Lymphocyte Culture by Uremic Adherent Spleen Cells and Peritoneal Macrophages Is Dependent on a Cyclophosphamide-Sensitive Cell

Abstract: A model of experimentally induced uremia in the rat has been used to study the effect of uremia on the response of spleen cells to alloantigens. The proliferative ability of uremic spleen cells in mixed lymphocyte culture is significantly suppressed when compared to that of cells from control animals. This suppression appears to be due to both adherent suppressor cells which can be eliminated by adherence to rayon wool and to the inability of uremic T cells to respond to alloantigens. In addition, unstimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…An abnormally increased SC activity has been re ported in the lymphocytes from uremic patients [11] and animals [12]. Whether this SC activity is induced, partially or completely, by the in vivo effects of the re spective uremic sera remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An abnormally increased SC activity has been re ported in the lymphocytes from uremic patients [11] and animals [12]. Whether this SC activity is induced, partially or completely, by the in vivo effects of the re spective uremic sera remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated an abnormally increased spontaneous suppressor cell (SC) activity in peripheral blood mononuclear cells (PBMC) from uremic patients [11] and in spleen cells from experi mentally uremic animals [12], Moreover, it has recently been shown that sera from uremic animals [13] or from patients on chronic hemodialysis [14] can induce SC activity in normal lymphocytes. However, Chandy et al [15] found that PBMC from patients, immediately following dialysis, acquired an increased SC activity which was correctable following depletion of adherent cells.…”
mentioning
confidence: 99%